2004
DOI: 10.1016/j.orthres.2004.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells used for rabbit tendon repair can form ectopic bone and express alkaline phosphatase activity in constructs

Abstract: Mesenchymal stem cells (MSCs) have been used to repair connective tissue defects in several animal models. Compared to "natural healing" controls (no added cells), MSC-collagen gel constructs in rabbit tendon defects significantly improve repair biomechanics. However, ectopic bone forms in 28% of MSC-treated rabbit tendons. To understand the source of bone formation, three studies were performed. In the first study, the hypothesis was tested that MSCs delivered during surgery contribute to bone formation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
148
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(151 citation statements)
references
References 20 publications
(22 reference statements)
3
148
0
Order By: Relevance
“…23 For tendon repair, previous studies in rodents showed that at least 10 6 BMSCs were required, 3,5,24 so it is not surprising that many more cells are needed in human patients. An optimized strategy for the in vitro expansion of stem cells while maintaining their undifferentiated stem cell characteristics is therefore essential.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 For tendon repair, previous studies in rodents showed that at least 10 6 BMSCs were required, 3,5,24 so it is not surprising that many more cells are needed in human patients. An optimized strategy for the in vitro expansion of stem cells while maintaining their undifferentiated stem cell characteristics is therefore essential.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest in recent years is the use of adult mesenchymal stem cells (MSCs) to regenerate functional tendons, [3][4][5] but ectopic bone formation after transplantation of bone marrow-derived MSCs (BMSCs) has been reported. 3,6 There has also been evidence of tumor induction by undifferentiated BMSCs in some specific circumstances. 7 Recently, multipotent stem cells, called tendon-derived stem cells (TDSCs), have been isolated from tendons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, various cell types have been utilized in meniscus tissue engineering [8][9][10], such as adult stem cells [bone marrow mesenchymal stem cells (BMSCs) and synovium-MSCs] and tissue-specific differentiated cell types (i.e., meniscal fibrochondrocytes). However, implanted BMSCs may lead to ossification if their osteogenesis is improperly induced at ectopic site [11]. Despite that synovium-MSCs have high chondrogenic potential and potentially serve as a reservoir of stem cells in the repair response [12,13], no notable differences of regenerated meniscus in morphology between the synovium-MSCs and the BMSCs have been found in a previous in vivo study [10].…”
Section: Introductionmentioning
confidence: 94%
“…For example, the present TGFβ3 delivery and controlled release may be useful in ligament regeneration in which ectopic bone formation has been found in the intended ligament portion [33]. The field of tissue engineering to date has focused primarily on single tissues such as skin, bone, muscle or cartilage.…”
Section: Discussionmentioning
confidence: 99%